ICTV Virus Taxonomy Profile: Sedoreoviridae 2022 - Matthijnssens, Jelle (2022)
Sedoreoviridae is a large family of icosahedral viruses that are usually regarded as non-enveloped with segmented (10–12 linear segments) dsRNA genomes of 18–26 kbp. Sedoreovirids have a broad host range, infecting mammals, birds, crustaceans, arthropods, algae and plants. Some of them have important pathogenic potential for humans (e.g. rotavirus A), livestock (e.g. bluetongue virus) and plants (e.g. rice dwarf virus). This is a summary of the ICTV Report on the family Sedoreoviridae, which is available at ictv.global/report/sedoreoviridae.